PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR HEALTHCARE - Halim, Jeanne Natalia; Hastuti, Rini Tri (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research will provide an alternative in estimating the fair price of a stock, especially in the healthcare sector, by considering the effect of Return on Assets (ROA) and Current Ratio (CR). In this study, data will be used for the annual financial statements of companies from 2018 - 2021 that are listed on the Indonesian Stock Exchange and have already conducted an Initial Public Offering (IPO). The data used in this study are 60 data each for ROA, CR, and stock prices when the Financial Statements are released to the public. Company data selection method is non-probability sampling with purposive sampling technique. This data processing and testing technique uses Eviews-12. The conclusion of this research are that ROA and CR have a significant influence either partially or simultaneously on the stock prices of health sector companies. These results were obtained by researchers using multiple linear analysis methods.